Health financing and expenditure in Nigeria (2013)
Health care financing policy has a significant impact on the structure and organization of health care delivery. The choice of a particular health care financing approach has implications for economic incentives to patients and the providers, variations in the extent of access to health care for particular population groups, and the organization of health care delivery. This paper addresses the concept and various methods of health financing, as well as the criteria for the choice of different health financing policies. It also analyzes Nigeria's health expenditure based on two rounds of estimates from the National Health Accounts of Nigeria (NHA), 1995 to 2002 and 2003 to 2005. While each of the major financing methods: government revenue, social and private insurance, user fees, and community financing has its own strengths and weaknesses, the choice a nation is largely dependent on its history, culture, and current institutions, and on whatever tradeoffs regarding objectives that nation is willing to make. The paper analysis health expenditure patterns in Nigeria, using the National Health Accounts, based on estimates from Soyibo (2005) and Soyibo et al. (2009). Total health expenditure, as a percentage of GDP over period 1998 to 2003 ranged between less than 5 per cent and 7.5 per cent, while the households account for the bulk (average of 66%) of financing health care in Nigeria, which is not sustainable. Government, who relies on tax revenue contribute less than 23 per cent of the country's total health expenditure, while industrial private sector and the donor agencies play a minimal role. To ensure sustainability of the funding of health expenditure in the country, there is a need for a gradual and progressive shift to risk pooling mechanism, which not only appears more viable and sustainable, but also tend to lighten the burden on the households. Government in addition should wake up to her stewardship role in funding health care to improve the general welfare of Nigerians.